Sources for beyond extreme ultraviolet lithography and water window imaging. (30th April 2015) - O'Sullivan, Gerry; Li, Bowen; Dunne, Padraig; Hayden, Paddy; Kilbane, Deirdre; Lokasani, Ragava; Long, Elaine; Ohashi, Hayato; O'Reilly, Fergal; Sheil, John; Sheridan, Paul; Sokell, Emma; et al.
Abstract: Lithography tools are being built and shipped to semiconductor manufacturers for high volume manufacturing using extreme ultraviolet lithography (EUVL) at a wavelength of 13.5 nm. This wavelength is based on the availability of Mo/Si multilayer mirrors (MLMs) with a reflectivity of ∼70% at this wavelength. Moreover, the primary lithography tool manufacturer, ASML, has identified 6. x nm, where x ∼7, as the wavelength of choice for so-called Beyond EUVL, based on the availability of La/B4 C MLMs, with theoretical reflectance approaching 80% at this wavelength. The optimum sources have been identified as laser produced plasmas of Gd and Tb, as n  = 4– n  = 4 transitions in their ions emit strongly near this wavelength. However, to date, the highest conversion efficiency obtained, for laser to EUV energy emitted within the 0.6% wavelength bandwidth of the mirror is only 0.8%, pointing to the need to identify other potential sources or consider the selection of other wavelengths. At the same time, sources for other applications are being developed. Conventional sources for soft x-ray microscopy use H-like line emission from liquid nitrogen or carbon containing liquid jets which can be focused using zone plates. Recently the possibility of using MLMs with n  = 4− n  = 4 emission from a highly charged Bi plasma was proposed and subsequently the possibility of using Δn  = 1 transitions in 3rd row transition elements was identified. All of these studies seek to identify spectral features that coincide with the reflectance characteristics of available MLMs, determine the conditions under which they are optimized and establish the maximum conversion efficiencies obtainable. Thus, there is a need for systematic studies of laser produced plasmas of a wide range of elements as some of the challenges are similar for all of these sources and some recent results will be presented.